2020
DOI: 10.3390/w12112985
|View full text |Cite
|
Sign up to set email alerts
|

Drought or Severe Drought? Hemiparasitic Yellow Mistletoe (Loranthus europaeus) Amplifies Drought Stress in Sessile Oak Trees (Quercus petraea) by Altering Water Status and Physiological Responses

Abstract: European oak species have long been considered relatively resistant to different disturbances, including drought. However, several recent studies have reported their decline initiated by complex changes. Therefore, we compared mature sessile oak trees (Quercus petraea (Matt.), Liebl.) infested versus non-infested by hemiparasitic yellow mistletoe (Loranthus europaeus Jacq.) during the relatively dry vegetation season of 2019. We used broad arrays of ecophysiological (maximal assimilation rate Asat, chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
9
0
1
Order By: Relevance
“…The Special Issue we introduce consists of 11 original research papers [1][2][3][4][5][6][7][8][9][10][11] divided into three groups based on research interests, namely, 1. hydrological and atmospheric aspects of natural hazards in changing climate and environment, 2. ecophysiological and ecological water-related impacts of natural hazards, and 3. methodological approaches in natural hazard evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue we introduce consists of 11 original research papers [1][2][3][4][5][6][7][8][9][10][11] divided into three groups based on research interests, namely, 1. hydrological and atmospheric aspects of natural hazards in changing climate and environment, 2. ecophysiological and ecological water-related impacts of natural hazards, and 3. methodological approaches in natural hazard evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, during the seed-to-seedling transition of any seed, metabolism is maintained by protein catabolism [ 85 ], and photosynthetic transcripts are down-regulated in both parasitic and other plants [ 128 ]. Chlorophyll and nitrogen contents from seedling establishment to adult life stages have been quantified in other Psittacanthus and mistletoe species [ 127 , 129 , 130 , 131 , 132 ]. Protease activity is directly related to protein catabolism, which in consequence impacts in the nitrogen and chlorophyll content in seeds, germination, and seedling development in P. calyculatus , which are development programs previous to seedling establishment [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mistletoes had lower N concentrations than hosts (a marginal significance of P = 0.090) in our study, which agrees with previous studies showing that mistletoes have similar (Bannister et al ., 2002; Scalon et al ., 2013; Scalon & Wright, 2015) or lower N than their hosts (Kubov et al ., 2020; Richards et al ., 2021). Also, we found that there were no differences in leaf Ca, Mg, and S concentrations between mistletoes and hosts, which is in line with some previous findings (Goldstein et al ., 1989; Bannister et al ., 2002; Scalon et al ., 2013; but see Glatzel, 1983; Lamont, 1983; Gebauer et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%